2010
DOI: 10.1007/s10526-010-9280-3
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism of the house fly parasitoid Spalangia cameroni on Norwegian pig farms: local effect of release method

Abstract: Mass release of parasitoids (Hymentoptera: Pteromalidae) is one possible control method of house flies (Musca domestica L.) on livestock farms. To improve the success of this method, however, there is a need for more detailed recommendations. In the present study, parasitism was evaluated in and around pens following release of the parasitoid Spalangia cameroni Perkins by hand and from containers. The study was conducted at conventional Norwegian pig farms with scattered breeding grounds for house flies. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Although we cannot exclude the possibility of laboratory-induced differences between the populations, a genetic component might also explain the differences. A far less accurate estimation of sex ratio from mass-produced S. cameroni that originated from the Danish strain yielded 60-62% female (Birkemoe et al 2009;Birkemoe and Øyrehagen 2010), which is fairly close to the present results. A study of the two populations under mass-rearing conditions is needed to determine whether the differences are maintained.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although we cannot exclude the possibility of laboratory-induced differences between the populations, a genetic component might also explain the differences. A far less accurate estimation of sex ratio from mass-produced S. cameroni that originated from the Danish strain yielded 60-62% female (Birkemoe et al 2009;Birkemoe and Øyrehagen 2010), which is fairly close to the present results. A study of the two populations under mass-rearing conditions is needed to determine whether the differences are maintained.…”
Section: Discussionsupporting
confidence: 89%
“…One plausible explanation for these differences in development time and survival could be the different adaptations to thermal regimens in the two populations' home ranges. The Norwegian population of S. cameroni was obtained from a confined pig production unit with moderate fluctuating indoor temperatures (17-24°C) from spring in April to autumn in September (Birkemoe et al 2009;Birkemoe and Øyrehagen 2010) and indoor temperatures of approximately 17°C in the winter months, according to farmers. The Danish population of S. cameroni originated from relatively open dairy cattle units with larger yearly fluctuating temperatures of 7-10°C in winter and 10-23°C in spring through the summer and autumn periods (Skovgård and Nachman 2004;Skovgård 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, Birkemoe & Oyrehagen (2010) conducted the only study comparing the 2 methods and found no significant effect on house fly parasitism by S. cameroni on Danish pig farms. They suggested that any disadvantages of the scatter method were compensated for by the short distance that parasitoids needed to travel to find hosts (Birkemoe & Øyrehagen 2010). Our results support the practice of scattering parasitized puparia in that the presence of formerly parasitized hosts does not interfere substantially in the ability of S. cameroni and M. raptor to locate and parasitize live puparia.…”
Section: Treatment (% Decoys)supporting
confidence: 74%
“…The lack of efficacy in some of these trials may be a consequence of insufficient knowledge to develop release protocols, including optimal distance between release sites or stations. Two common parasitoid release methods are scattering parasitized host puparia on the ground near fly development sites [ 22 24 ] and allowing parasitoids to disperse from artificial devices placed in or near known fly development areas [ 16 , 21 , 22 23 ]. In some release studies, the distance between release stations is not given or the method of release is not disclosed.…”
Section: Introductionmentioning
confidence: 99%